Effectiveness of PMRI Assisted by VERULI on Elementary School Students' Mathematical Problem-Solving Skills - Aulia Khairunnisa Supardi; Maulana Maulana; Isrok'atun Isrok'atun (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Mathematical problem-solving is an essential competency, yet many elementary students struggle due to limited conceptual understanding and difficulty relating mathematics to real-life contexts. Therefore, more meaningful learning approaches and media are needed to support their understanding. This study aimed to analyze the effectiveness of the Indonesian Realistic Mathematics Education (PMRI) approach assisted by VERULI media (Liter Volume Conversion Space), which is a manipulative medium in the form of various bottle sizes used to concretely visualize the process of volume unit conversion, on the mathematical problem-solving skills of fourth-grade elementary school students. The study used a quasi-experimental method with a nonequivalent control group design. Participants were selected through purposive sampling, involving 101 fourth-grade students from three schools. Data were collected using problem-solving tests, learning observation sheets, and student response questionnaires, and analyzed using the Kruskal–Wallis test and N-Gain calculation. The results showed that there was no significant difference in mathematical problem-solving skills among the groups based on the Kruskal-Wallis test (p=0,069). Nevertheless, the group that received PMRI learning assisted by VERULI media demonstrated the highest improvement in skills with an N-Gain value of 0,4281 (moderate category), compared to the PMRI group at 0,3199 and the conventional learning group assisted by VERULI media at 0,4052. The observation results indicated that all stages of learning were implemented very well. Furthermore, student responses to the learning were classified as positive, with a percentage of 84% in the PMRI group assisted by VERULI media, 75% in the PMRI group, and 78% in the conventional group assisted by VERULI media. These findings indicated that the PMRI approach assisted by VERULI media was effective in improving students' mathematical problem-solving skills on the topic of volume unit conversion.